2020
DOI: 10.3390/ijerph17217937
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t You Think It Is Violence Forcing Me to Have Sex While Not Happy?” Women’s Conceptualization of Enjoyable Sex and Sexual Intimate Partner Violence in Mwanza, Tanzania

Abstract: Intimate partner violence is a recognized public health and development issue that is consistently and comparatively measured through women’s experience of physical and/or sexual acts by their partner. While physical intimate partner violence is covered by a wide range of behaviors, sexual intimate partner violence (SIPV) is often only measured through attempted or completed forced sex, ignoring less obvious forms of sexual intimate partner violence. We explored women’s conceptualizations of SIPV by conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Data was collected between July and September 2020. The recruitment procedures of the participants involved in this study has been described in detail elsewhere [ 10 , 11 ], but in summary, a total of 18 women aged 27 to 57 years were purposively selected to participate in qualitative telephone in-depth interviews. These women were selected from 85 women participating in the longitudinal mixed methods MAISHA study [ 12 ] who reported changes in their experiences of sexual intimate partner violence between the baseline and endline survey of the MAISHA trial.…”
Section: Methodsmentioning
confidence: 99%
“…Data was collected between July and September 2020. The recruitment procedures of the participants involved in this study has been described in detail elsewhere [ 10 , 11 ], but in summary, a total of 18 women aged 27 to 57 years were purposively selected to participate in qualitative telephone in-depth interviews. These women were selected from 85 women participating in the longitudinal mixed methods MAISHA study [ 12 ] who reported changes in their experiences of sexual intimate partner violence between the baseline and endline survey of the MAISHA trial.…”
Section: Methodsmentioning
confidence: 99%
“…In communities still subscribing to patriarchal ideals, men exercise more power and may resort to violence to enforce their authority (Howard-Merrill et al, 2022;Manji, 2018). In such settings, gender norms prescribe that women should acquiesce to her male partner's sex urges with the only exception being that they are sick or having their menstrual periods (Mchome et al, 2020). Also, women are expected to be faithful to their partners while it is the norm for men to have multiple sexual relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Although romantic jealousy is present across all cultures and societies, it is highly dependent on the context in its interpretation ( Buss, 2013 ). It can lead to the loss of self-control, especially when partners who suspect or confirm infidelity are unable to regulate their emotions and reactions ( Mužinić et al, 2003 ). On the other hand, romantic jealousy is also often interpreted by men and women in relationships as an expression of love, and a sign that a partner cares about the other and the relationship ( Boyce et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…These women were sampled from a pool of 85 women who reported changes in their experiences of sexual IPV between the baseline and endline survey of the trial. Changes in sexual IPV were chosen because they are a manifestation of severe IPV in a couple (Mchome et al, 2020). The purposive sampling ensured that women from different socioeconomic and cultural backgrounds were included, specifically from different ethnicities, religious groups, age groups, and with different income‐generating activities in Mwanza city (see Table 1).…”
Section: Methodsmentioning
confidence: 99%